2011
DOI: 10.1021/jz200708j
|View full text |Cite
|
Sign up to set email alerts
|

Fluid Flow and Effusive Desorption: Dominant Mechanisms of Energy Dissipation after Energetic Cluster Bombardment of Molecular Solids

Abstract: The angular distribution of intact organic molecules desorbed by energetic C60 primary ions was probed both experimentally and with molecular dynamics computer simulations. For benzo[a]pyrene, the angular distribution of intact molecules is observed to peak at off-normal angles. Molecular dynamics computer simulations on a similar system show the mechanism of desorption involves fast deposition of energy followed by fluid-flow and effusive-type emission of intact molecules. The off-normal peak in the angular d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
32
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 43 publications
2
32
1
Order By: Relevance
“…In addition to primary ion dependent variations in sputter yield, it is possible to measure the kinetic energy distribution of sputtered material using sophisticated photoionization techniques [20][21][22][23]. These methods can provide insight into the mechanism of energy transfer from the primary ion to the surface and sub-surface atoms.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to primary ion dependent variations in sputter yield, it is possible to measure the kinetic energy distribution of sputtered material using sophisticated photoionization techniques [20][21][22][23]. These methods can provide insight into the mechanism of energy transfer from the primary ion to the surface and sub-surface atoms.…”
Section: Resultsmentioning
confidence: 99%
“…Similar behavior has been reported more recently for benzene sample bombarded with 15 keV Ar 2953 . 5 Off-normal ejection also has been measured for intact benzopyrene molecules during C 60 bombardment, 6 although the effect is not as pronounced as observed for large Ar clusters. Recent experiments of Chernysh et al performed with Ar gas cluster projectiles on several polycrystalline metals and alloys, 7,8 in general, have confirmed observations of Yamada et al However, a different shape of angular distributions was observed when Mo and W surfaces were bombarded with 10 keV Ar 800 .…”
Section: Introductionmentioning
confidence: 98%
“…, a zone with fragmented molecules is surrounded by a volume from where the intact molecules are emitted. The mechanistic analysis shows that the emission process can be described by a concept of a fluid/gas flow motion, where most of intact molecules are emitted from the corona of the crater by material transport along the walls of the forming crater . Such spatial arrangement explains why so few fragments remain in the solid.…”
Section: Resultsmentioning
confidence: 99%